Copper(I) catalysed direct synthesis of 2-methylene-4-chromanols. Issue 1 (2nd January 2020) - Sarkar, Debayan; Behera, Sagarika
Graphical abstract: Highlights: Copper Catalysed atom-economic synthesis of 2-methylene chromanols. The reaction is an open flask reaction. No external ligand is necessary for this transformation. Satisfactory yields with di-halides and unprotected alcohols. Abstract: A copper catalyzed atom-economic synthesis of 2-methylene-4-chromanols has been described. The 2-methylene-4-chromanols act as an important entry points to a large section of biologically active motifs. The reaction delivers a wide substrate scope with moderate to excellent yields with substituted alkynes and in presence of unprotected alcoholic functionalities to deliver the 2-(2-hydroxy alkylidene)chroman-4-ols.